EFFECT OF UNEQUAL TRADE EXCHANGE ON ECONOMIC DEVELOPMENT IN IRAQ (2003-2018) - Abdulwahab M. Jawad Almusawi, Ali Abdullah Hussein Almusawy (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The paper aims to shed light on the nature of foreign exchange in Iraq with its trading partners between 2003 and 2018. This relationship reveals the degree of vulnerability and exposure of the Iraqi economy to countries around the world through the imbalance of commodity exchange. Iraq's foreign trade is dominated by a major commodity represented by crude oil and it is the security resource to finance domestic demand. There are challenges to that commodity represented in the inability of Iraq to control its financial revenues as a result of the fluctuations that occur in the global market. The lack of commodity products will definitely lead to the weakness of the local market’s ability to meet internal demand. The reason for this is the absence of a flexible productive apparatus for other economic sectors to interact with the changes that take place in domestic or foreign demand. This will open the door for commodity imports of all kinds to invade the Iraqi market without oversight or restrictions, in light of following the policy of trade openness. The results show that the average relative importance of non-oil merchandise exports is 1.5% of total exports. On the other hand, the size of the importer is 91%, which confirms the size of the unequal trade relationship in favor of the foreign country. In addition to the negative consequences of that relationship on the Iraqi economy, represented by strengthening structural imbalances in the productive sectors, increasing unemployment rates, enhancing public debt, increasing consumption levels and reducing the volume of savings, and then reducing the volume of investments needed to address those imbalances. As a result, the foreign investor's reluctance to have an acceptable investment climate.